Estudio de algunas areniscas de las formaciones San Cayetano y Polier, Sierra del Rosario, Cuba - Cobiella-Reguera, Jorge; Hernández-Escobar, Arturo; Díaz-Díaz, Niurka; Obregón-Pérez, Pavel (Minería y Geología, 2018)
hacer